A similitude relation to assessing the compressive strength of rammed earth from scale-down samples. (June 2022) - Pelé-Peltier, Antoine; Fabbri, Antonin; Morel, Jean-Claude; Hamard, Erwan; Lhenry, Maxime
Abstract: Rammed earth (RE) as a construction material fits perfectly into the circular economy concept as the soil is usually taken from excavation works (a waste) and is upcycled to build earthen architecture without adding any other components (unstabilised RE). RE is therefore recoverable at the building end-of-life. For non-common buildings, it is crucial to measure the compressive strength by lab testing on representative samples. While it is necessary to remove the biggest grains to manufacture standard size samples to achieve a homogeneous material, there is no research on how such samples are representative of the in situ RE. This paper develops a similitude relation to take into account the scale effect of the reduction of the size of the biggest grains of scale-down RE samples. The similitude relation is designed for the dry density, the manufacturing water content, and the grain size of the RE. Those parameters were first determined from the construction field of a case study, to define the equivalent parameters to manufacture the scale-down samples with three different grain sizes, capped at 12, 20, 30 mm for the earth; 50 mm being the maximum grain size of the earth used on-site. Compression tests were performed on 66 samples with samples of three different sizes, two geometries and four manufacturing water contents. The compressive strength using the scale-down granulometry samples designed with the similitude relation is similar to the strength of full-scale granulometry whatever samples size or geometry. For a given earth, the method using the similitude relation allows reducing the size of samples without hampering the representativeness of the results. This will help to reduce projects' costs. Graphical Abstract: ga1 Highlights: Compression tests on 66 rammed earth (RE) samples with the same clay-matrix but different gravel sizes. The grain size influence on the compressive strength of RE is examined. A similitude relation links the grain size, water content during the test and compressive strength. Applying the similitude relation allows using smaller samples with scale-down grain size.